UJI COBA PEMANFAATAN SARI DAUN KATUK (SAUROPUS ADROGYNUS (L) MERR) SUBTITUSI AIR KELAPA (COCOS NUCIFERA L.) DALAM PEMBUATAN NATA DE COCO - Abduh, Mohammad Syaltut; Adawiyah, Robiatul (Jurnal Ilmiah Pariwisata, 2019)
This research recommends using katuk leaf extract as a substitute for Nata de coco food as a nutritious processed food product for nursing mothers who are practical when consumed anywhere. Katuk plant (Sauropus adrogynus (L) Merr) is a type of herbaceous plant that grows chronically, is a vegetable plant that is found in Southeast Asia. The leaves are small like moringa leaves, small green flowers, dark red to yellowish, with red spots. The flower will produce white fruit where there are black seeds inside. Several studies have shown that katuk leaves can expedite milk production. With this research it is hoped that it can add to the processed variant of katuk leaf utilization. The method used in this research is to use a different test and a fondness test on several panelists who already understand and are familiar with Nata de Coco. For the different test results in terms of texture (0.006 <0.05) and taste (0.030 <0.05) this means that there is no difference in terms of texture and taste between the control and treatment of products.